A Chemically Doped Naphthalenediimide-Bithiazole Polymer for n-Type Organic Thermoelectrics - Wang, Suhao (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.